Consumo e aceitação das variedades de queijo emmental e minas frescal - Martynychen, Dayana Elisa Kubiak (2011)
The cheese market has a large number of consumers in all regions. According to research in Brazil 60% of cheese production meets the standards of Inspection of SIF and 40% of producers remain informal. Market research is the ideal instrument for the successful development of businesses, because they change with the demands of consumers. Sensory analysis and research are some of the online tools available to assess the degree of satisfaction and requirements of consumers. The trend of consumption among a fine cheese and a cheese common in this work is discussed by sensory analysis, and verified the acceptability of varieties of emmental and minas frescal. According the results, it is concluded that consumers generally have a strong tendency to consumption of these two types of cheese, both of which are approved by them. As results of the online survey, 53% of the participants know the two cheeses, but only 43% know frescal minas cheese. Thus, it is clear that the minas cheese frescal have wide acceptance and is being inserted in a meaningful way in the culture of the population. The emmental, needs wider dissemination and appreciation, with higher production and lower prices to stimulate and diversify the consumption of cheese by the population and boost sales.